1976
DOI: 10.1007/bf00426842
|View full text |Cite
|
Sign up to set email alerts
|

Serum dopamine-?-hydroxylase in psychiatric patients and normals. Effect of d-amphetamine and haloperidol

Abstract: Serum dopamine-beta-hydroxylase activity was estimated in groups of normals and of psychiatric patients, using a thin layer radiochromatographic method. The percentage of patients with schizophrenic and with depressive symptomatology was higher in the population with high enzyme activities. In addition, d-amphetamine given to normals caused an increase in the serum activity while haloperidol caused the opposite effect. The activity in serum is interpreted as a loss in the enzyme from the place it acts physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The relationship between DBH activity and neuroleptic therapeutic response was studied by several investigators. Markianos et al [1976] found that, compared to controls, a higher proportion of schizophrenic patients present increased serum DBH activity that was insensitive to the inhibitory effect of haloperidol. In contrast, other investigators [Sternberg et al, 1982; Van Kammen et al, 1983] showed that schizophrenic patients with low CSF levels of DBH exhibited more acute psychotic symptoms and appeared to be more responsive to standard antipsychotic medications.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between DBH activity and neuroleptic therapeutic response was studied by several investigators. Markianos et al [1976] found that, compared to controls, a higher proportion of schizophrenic patients present increased serum DBH activity that was insensitive to the inhibitory effect of haloperidol. In contrast, other investigators [Sternberg et al, 1982; Van Kammen et al, 1983] showed that schizophrenic patients with low CSF levels of DBH exhibited more acute psychotic symptoms and appeared to be more responsive to standard antipsychotic medications.…”
Section: Discussionmentioning
confidence: 96%
“…It has long been proposed that DBH activity alters in patients with mental illness, especially those with affective disorder or schizophrenia, although the findings to data have been inconsistent (Wise and Stein 1973;Wyatt et al 1975;Markianos et al 1976;Melter et al 1976;Fujita et al 1978;van Kammen et al 1983;Wei et al 1992). DBH deficiency has also been reported in some neurological or physical diseases in humans (Biaggioni et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between this study and our data might be explained by the fact that our study included larger groups of war veterans, and that plasma DBH activity was higher in subjects carrying CC genotype of the DBH −1021C/T polymorphism, which was not assessed in the Hamner and Gould (1998) study. Aside from different genotypes, lower plasma DBH activity might be affected by previous medication, as exposure to neuroleptics decreases plasma DBH activity (Markianos et al, 1976). Since our subjects were medication‐free, the possible effect of neuroleptics on plasma DBH activity was excluded.…”
mentioning
confidence: 99%